2021
DOI: 10.1097/dbp.0000000000001050
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Associations Among Perceived Stress, Self-Control Skills, and Overeating in Asian Adolescents

Abstract: Objective: Built on Rosenbaum's self-control theory, this study aimed to examine the mediating role of self-control skills in the relationship between perceived stress and overeating patterns among adolescents from an Asia-Pacific region. Methods: A cross-sectional study was used with a school-based, nonclinical sample of 195 adolescents. Participants completed self-report measures assessing study variables and demographic information such as body mass index (BMI) status for adolescents and their parents. Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…The association between FA symptoms and self-control reported in this study is consistent with the findings of recent studies, suggesting that self-control may be a contributing factor to unhealthy eating behaviours, including FA [17,23,62]. A study by Luo et al (2022), which comprised a cohort of college students, found a significant negative correlation between self-control and FA [63], while other studies of adult populations with FA have reported similar findings of reduced self-control [64,65].…”
Section: Discussionsupporting
confidence: 92%
“…The association between FA symptoms and self-control reported in this study is consistent with the findings of recent studies, suggesting that self-control may be a contributing factor to unhealthy eating behaviours, including FA [17,23,62]. A study by Luo et al (2022), which comprised a cohort of college students, found a significant negative correlation between self-control and FA [63], while other studies of adult populations with FA have reported similar findings of reduced self-control [64,65].…”
Section: Discussionsupporting
confidence: 92%